FINANCIAL TECHNOLOGY AND ITS RELATIONSHIP TO INDICATORS OF SUSTAINABLE DEVELOPMENT WITH SPECIAL REFERENCE TO IRAQ - Asst.Prof.Dr.Ahmed H.Al-Husayny (American Journals, 2022)
Financial technology as an experience in the banking sector is a recent financial experience. The current study examines the ability of the banking sector to contribute to achieving the requirements of sustainable development through the role of modern technology in enabling various social groups to own electronic services and use them to meet their requirements. This will contribute to the advanced stages of achieving the seventeenth sustainable development goals. The search will focus on Iraq and how many financial technology requirements will support sustainable development requirements.
Keywords: Financial technology, Banking sector, Sustainable development